Z zagadnień aktywności fizycznej, zdrowia, promocji zdrowia i higieny na wsi w Polsce do 1939 roku = Physical education, health, health promotion, and hygiene in Polish villages till 1939 - selected issues - Małolepszy, Eligiusz; Drozdek-Małolepsza, Teresa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present issues of physical activity, health, health promotion, and hygiene in Polish villages till 1939. Activity in these areas was implemented by Państwowy Urząd Wychowania Fizycznego i Przysposobienia Wojskowego (the State Office of Physical Education and Civil Defense) and its administrative structures, Rada Naukowa Wychowania Fizycznego (Scientific Council of Physical Education), rural youth organizations and the press they published, agricultural schools, and Wiejskie Uniwersytety Ludowe (People's Rural Universities). Activity in the fields of physical education, health, and hygiene were implemented in the educational, training, and pedagogical aspects. Hygiene and physical education courses promoting hygiene and hygiene with rescue training were organized for village dwellers, especially for young people.
Keywords: zdrowie; promocja zdrowia; higiena; wieś; health; health promotion; hygiene; village